18th century clothing - Kalman, Bobbie (New York : Crabtree Pub. Co., 1993)
This book examines the clothing styles, accessories, and hygiene habits of men, women, and children in eighteenth century North America.
Includes index.
10 years
72495
Keywords: Costume -- History -- Juvenile literature; Costume -- History -- Juvenile literature. -- 18th century; Costume -- History -- 18th century